Detection of leukaemia-associated aberrant immunophenotype (LAIPs) in acute leukaemia and its association with haematological parameters and treatment outcome - Rahman, Noor Shaidatul Akmal Ab (2017)
Acute leukaemia is one of the commonest haematological malignancies worldwide. Presence of specific and different antigen expressions of leukaemic cells at initial presentation help in establishing the diagnosis and specify the lineage involved. These leukaemic cells may express leukaemia-associated aberrant immunophenotype (LAIPs) at diagnosis. Studies have been done to look for association of these LAIPs with known haematological parameters and the results are various. These LAIPs also has been used as a marker for assessment of residual disease following respective chemotherapy. Many modalities have been developed for its assessment. One of the sensitive and convenient methods is multicolour flow cytometry. The aim of this study was to identify the frequency of LAIPs in acute leukaemia patient in local as well as to look for the association of these markers with sociodemographic data, haematological parameters and remission status (post induction chemotherapy). A retrospective cohort study was done by collecting 134 samples of acute leukaemia patient diagnosed in HUSM during the study period. The samples were analysed for immunophenotyping using 4-colour flow cytometry and correlate with patients’ sociodemographic data, complete blood count, bone marrow aspirate, cytogenetic findings as well as morphologic remission status post induction chemotherapy. From 134 samples analysed, both acute myeloid leukaemia (AML) and B acute lymphoblastic leukaemia (BALL) were diagnosed in 62 patients each and T acute lymphoblastic leukaemia (TALL) seen in 10 cases. In AML, CD56 is the most common LAIPs marker found followed by CD7, CD2, CD19 and cyCD79a. Whereas, CD 13 is the most common LAIPs found among BALL cases followed by CD56, CD2, CD117, CD16, CD11b and CD4. In TALL, both CD13 and CD117 is the most common LAIPs marker found followed by CD33, CD71,CD64, CD11b and cyCD79a. From this study also, showed CD33 had significant association with gender in BALL. Other than that in AML, CD2 had significant association with age group and CD7 had significant association with gender and platelet count. From this study, significant number of acute leukaemia patient in local demonstrate presence of LAiPs at diagnosis and this is useful for establishing our own immunophenotyping panels for monitoring residual disease following chemotherapy. Certain markers had significant association with haematological parameters analysed.